Selection of Materials for Repairing Punctures of Metal Skin of Semi-monocoque Structures Using Composite Patches - Iga Barca; Marek Rośkowicz; Jan Godzimirski (Technologia i Automatyzacja Montażu)
For repairing punctures of skin of semi-monocoque structures under field conditions, simple methods are sought to guarantee the reliability of the repaired structure. Therefore, adhesive joints and composite materials are being increasingly used in repairs. During repairs using adhesion, an important aspect that affects the quality of the joint is the selection of the adhesive and the quality of surface preparation of the parts to be joined. This is necessary to get the right bond strength and durability of the joint in working environments characterized by extreme temperatures and exposure to chemicals and moisture. The purpose of the study was to select an adhesive with good strength properties for bonding AW2024T3 aluminum sheets to carbon and glass composites, and to analyze the effect of metal surface preparation on the strength of adhesive joints (grinding, sandblasting and chemical surface preparation). The tests were carried out on overlap (metal-composite) specimens. For selected adhesives, strength tests were also carried out on specimens replicating the repaired damage with a diameter of 20 mm of metal skin repaired by different methods, including composite patches and adhesive joints. The specimens were loaded in tension and loss of stability. The tests made it possible to determine the requirements for composite patches used for repairing upper and lower airframe wing skins.